Strategi Pengembangan Objek Wisata Pantai Sunari Sebagai Tujuan Wisata di Kabupaten Kepulauan Selayar - Harpin, Irma Rahmayani; Akhmad, Akhmad; Suarni, Agusdiwana (Universitas Teuku Umar, 2025)
The study aims to indentify the right strategies to make Sunari Beach an advanced and attractive tourist destinasion for local and foreign tourists. The focus of this study is internal dan external factors in determining the development strategy of Sunari Beach tourism. Data were obtained from 12 informants, namely Sunari Beach staff, Patikarya village mother, visitors and the surrounding community through interviews and analyzed using qualitative descriptive and swot analysis. The result of the study indicate that the right strategy in developing Sunari Beach tourism based on sowt analysis in the opportunity strategy, namely by maximzing strengths and opportunities through the development of tourism activity facilities and following tourism trends. Threats strategy, namely optimizing strengths to reduce the impact of climate change and overturism with an environmentally friendly approach and tourist segmentation. Weakness opportunity strategy, namely reducing weaknesses and facing threats by diversifying income and personalized touris services. These findings indicate that the development of Sunari Beach as a highly competitive touris destinastion can be achieved through a collaborations strategy and opportunities and challenges in the field. Therefore, by help develop the Sunari Beach tourist attraction and be able to compete with other destination. Keywords: Sunari Beach, Development Strategy, SWOT Analysis